Influência dos argumentos ecológicos no consumo de tecnologia da informação - Zwicker, Ana Amélia Moura (2017)
Information Technology (IT) is deeply rooted in development on a global scale. Because of this, addressing consumption in the perspective of Green IT is very important in facing the challenges to achieving environmental sustainability. Therefore, the objective of this work was to verify the influence of ecological arguments on the consumer's intention to purchase information technology. Three main areas were considered: Green Information Technology (Sustainability and IT), Green Marketing and Decisional Process. In a complex design, two quasi-experiments were applied in two types of environment: field (study design: 1 control group and 1 experimental group) and laboratory (2 x 2 x 3 factorial design). In addition to presenting the differential of the comparison of the results in two environments, the research stands out by the association of theories of the Cues with the one of the Anchoring-and-Adjustment Heuristic, relation not found in the academic literature. In addition, it includes the Sustainable Consumption approach in the two predictive models of IT buying intent: one for ad A (with ecological argument) and one for ad B (with no ecological argument). The subjects of experiment 1 were formed by consumers of an information technology shop and experiment 2 contained undergraduate students of Sanitary and Environmental Engineering, Administration and Information Systems of a Federal University, totaling 274 respondents from Brazil. Through the quantitative and qualitative analysis, the main results suggest that, in the field study, there was a significant difference of 5% (p = 0.05) with respect to the intention to buy (Ic), and subjects who analyzed ad A (with the ecological argument - AE) had a higher Ic than those who analyzed ad B (without AE). In the laboratory study, no statistically significant differences were found in relation to attitudes without the video manipulation (anchoring). The results in the latter study indicate a higher sustainable discourse than a purchasing intention per se: students generally strongly referred to the ecological argument as the more observed product aspect taken into account in the advertisement, but this was not reflected in their attitudes. Still, in relation to the group of students, evidence suggests that the accessibility of knowledge interferes the final adjustment of the anchor of the Anchorage Heuristic: pairing of the courses affected the attitudes of the individuals in relation to the video display. Regarding the regression analysis, we found the only variable of the sustainable consumption construct that affected the purchase intention in advertisement A was related to the reuse of objects.